Customer's quest for quality of products and services offered by farmers' organization / Sarina Muhamad Noor ... [et al.] - Muhamad Noor, Sarina; Nasirun, Noraini; Abduljabbar Sultan, Abdulsatar; Mohamed, Jaaffar (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
Quality products and services are paramount in every organization as satisfied customers are the key element for their existence. Moreover, studies have discovered that customers are the heart of all organisations regardless of their entity. The emergence of farmers association as a non-profit organization is to reduce the transaction cost of its members and to help in providing quality food production. Nevertheless, limited study was found that explained the quality of products and services of such organisations. Majority of the previous studies have focused on manufacturing and services of private organisations. Therefore, this study was conducted to investigate the quality of products and services offered by a farmers' organization, namely Pertubuhan Peladang Kawasan in Malaysia. Their customers are the government agencies that purchased poultry products. In order to achieve the objective, a case study approach using a structured interview was conducted with ten agencies. The information provided by these agencies was analysed and compared with previous literatures. Findings showed that most of the customers are dissatisfied on the assurance and responsiveness, with only 50% were satisfied with the products and services provided by this association. Surprisingly, most customers will continue to maintain relationship with Pertubuhan Peladang Kawasan. These findings are parallel with the suggestion made by literatures that the complex dimension of customers' supplier relationship attributes to their repeat purchase. This study provides an initial attempt to measure the quality of products and services offered by one of the farmer's organisations in Malaysia. A discussion on the study and its implications are discussed at the end of the article.